1994
DOI: 10.1177/030089169408000109
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Interstitial Brachytherapy for Glioblastoma Multiforme

Abstract: Our approach seems to be of some interest for the palliation of GBL, and it offers some advantages, in particular regarding the short treatment period. Our procedure can be improved: a multi-catheter implant and a more fractionated schedule could be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Although a considerable number of anatomic sites have been treated successfully with HDR-BRT and there is no significant medical or radiobiological evidence against its use in central nervous system lesions [29,36,58], LDR is still consid- ered the standard modality in recurrent GBM. Results from several studies using LDR are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Although a considerable number of anatomic sites have been treated successfully with HDR-BRT and there is no significant medical or radiobiological evidence against its use in central nervous system lesions [29,36,58], LDR is still consid- ered the standard modality in recurrent GBM. Results from several studies using LDR are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…This may account for the lower rate (6%) of moderate to severe complications in HDR studies (Tselis et al 2007), compared to up to 26% in LDR studies and even higher when BRT was combined with hyperthermia (Table 1) (Bernstein et al 1994;Halligan et al 1996;Patel et al 2000;Shrieve et al 1995;Sneed et al 1992). Additionally, HDR techniques can palliate patients with non-resectable lesions or poor functional scores without external beam radiation (EBRT), in order to reduce the overall hospitalization and (Micheletti et al 1994(Micheletti et al , 1996 The authors concluded that together with decreased total treatment time (<7 days), the overall survival was equal or better than comparable patients received EBRT Micheletti et al 1994Micheletti et al , 1996.…”
Section: Controversy 2: High-dose Rate Vs Low-dose Ratementioning
confidence: 99%
“…Initially, BRT for malignant gliomas is performed after the completion of EBRT or at the time of disease recurrence; however, several recent studies have explored the administration of BRT as upfront treatment at the time of diagnosis prior to EBRT (Micheletti et al 1994(Micheletti et al , 1996. Use of cytoreductive procedures prior to initiating treatment is the underlying rationale supported widely, though this rationale itself remains questionable with its beneWt elusive from the literature for aggressive surgical resections (Lacroix et al 2001;Simpson et al 1993).…”
Section: Controversy 6: Timing Of Brachytherapymentioning
confidence: 99%